2011
DOI: 10.1007/s11708-011-0157-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oxygen enriched combustion on the performance of a single cylinder diesel engine

Abstract: In the present experiment, a computerized single cylinder diesel engine with a data acquisition system was used to study the effects of oxygen enriched combustion technology (OECT) on the performance characteristics. The use of different levels of oxygenenriched air was compared with respect to percentage load. Increasing the oxygen content in the air leads to faster burn rates and increases the combustibility at the same stoichiometry (oxygen-to-fuel ratio). These effects have the potential to increase the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This result agrees well with the study by Monirul et al, who reported a 4.19% increase in BP when 10% POB was added to diesel compared to pure diesel. This is due to the increase in O 2 content, in the fuel molecule of the fatty acid in POB, resulting in a more effective combustion. , In addition, the lower density and viscosity of B10 can influence the power loss due to higher leakages at the fuel pump compared with WPO100 . Meanwhile, Ali et al reported a decrease of 0.49% in BP by adding 10% POB to diesel compared to pure diesel.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This result agrees well with the study by Monirul et al, who reported a 4.19% increase in BP when 10% POB was added to diesel compared to pure diesel. This is due to the increase in O 2 content, in the fuel molecule of the fatty acid in POB, resulting in a more effective combustion. , In addition, the lower density and viscosity of B10 can influence the power loss due to higher leakages at the fuel pump compared with WPO100 . Meanwhile, Ali et al reported a decrease of 0.49% in BP by adding 10% POB to diesel compared to pure diesel.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The schematic above is highly simplified, and it attempts to depict changes of the liquid–wall interactions and impinging flame morphology under different altitude conditions only based on the results discussed in this work. However, it can furnish the diesel engine community with a mental image to promote new thinking beyond the popular solutions, such as two-stage turbocharger systems, alternative fuels, oxygen enrichment of the intake air, adjusted injection systems, and advanced injection strategies, to recover and improve the performance of diesel engines operating in plateau regions. Herein, we attempt to analyze two viewpoints.…”
Section: Role Of Altitude In Spray Combustion Process Of Impinging Di...mentioning
confidence: 99%
“…So the higher output of exhaust gas is the simplest form to study the combustion efficiency [14] . Higher oxygen levels in mixture can increase the combustion rate and high compression ratios also increase the temperature by increasing the pressure resulting higher temperatures of exhaust gas due to more complete combustion [15] .…”
Section: E Exhaust Gas Temperaturementioning
confidence: 99%